Prebiotic potential of water extractable polysaccharide from red kidney bean (Phaseolus vulgaris L.). (March 2019) - Jayamanohar, Jabastin; Devi, Palanisamy Bruntha; Kavitake, Digambar; Priyadarisini, Venkatesan Brindha; Shetty, Prathapkumar Halady
Abstract: Red kidney bean ( Phaseolus vulgaris ) is an excellent source of proteins, complex carbohydrates, fermentable fibers, antioxidant, vitamins and minerals loaded with ample of health benefits. This study assesses in vitro prebiotic potential, fecal fermentation and antibiofilm activity of water extractable polysaccharides (RKBWEP) from red kidney bean ( Phaseolus vulgaris ). RKBWEP exhibited lower digestibility to pretended human gastric juice (1.58%), α-amylase (4.68%) and intestinal fluid (4.03%) hydrolysis than standard fructooligosaccharide as 2.04%, 5.6% & 7.13% respectively. RKBWEP significantly stimulated the growth of standard probiotic bacteria Lactobacillus plantarum and L. fermentum . In vitro batch fecal fermentation of RKBWEP stimulated growth of beneficial gut microbiota especially Bifidobacterium spp. and Lactobacillus spp. after 24 h. Short chain fatty acids (SCFAs) such as acetic acid, propionic acid and butyric acid concentration increased during RKBWEP fermentation and reached maximum of 47.92, 10.32, 6.91 mM after 48 h. Moreover, RKBWEP (40 μg) effectively inhibited Escherichia coli biofilm formation by 79%. Potential prebiotic and biofilm inhibiting property of kidney bean polysaccharide could be explored as novel food grade adjuncts targeted towards synbiotics development. Graphical abstract: Highlights: Red kidney bean water extractable polysaccharides (RKBWEP) have prebiotic properties. RKBWEP were high resistant to α-amylase, gastric, intestinal juice hydrolysis. RKBWEP enhanced the growth of probiotic bacteria ( L. plantarum & L. fermentum ). In vitro fecal fermentation of RKBWEP showed high production of SCFAs (63.4 mM). Biofilm inhibition (79%) of Escherichia coli by 40 μg RKBWEP.